China's policy towards the South China Sea when geopolitics meets the law of the sea - Li, Lingqun (Contemporary issues in the South China Sea, 2018)
"This book provides an explanation of Chinese policy towards the South China Sea, and argues that this is sculpted by the changing dynamics of the law of the sea in conjunction with regional geopolitical flux"--Provided by publisher.